Transforming information security governance in India (A SAP-LAP based case study of security, IT policy and e-governance). (12th March 2018) - Anand, Rashmi; Medhavi, Sanjay; Soni, Vivek; Malhotra, Charru; Banwet, D.K.
Abstract : Purpose: Digital India, the flagship programme of Government of India (GoI) originated from National e-Governance Project (NeGP) in the year 2014. The programme has important aspect of information security and implementation of IT policy which supports e-Governance in a focused approach of Mission Mode. In this context, there is a need to assess situation of the programme which covers a study of initiatives and actions taken by various actor involved and processes which are responsible for overall e-Governance. Therefore, the purpose of this case study is to develop a Situation-Actor-Process (SAP), Learning-Action-Performance (LAP) based inquiry model to synthesize situation of information security governance, IT policy and overall e-Governance. Design/methodology/approach: In this case study both systematic inquiry and matrices based SAP-LAP models are developed. Actors are classified who are found responsible and engaged in IT policy framing, infrastructure development and also in e-Governance implementation. Based on a synthesis of SAP components, various LAP elements were then synthesized then which further led to learning from the case study. Suitable actions and performance have also been highlighted, followed by a statement of the impact of the efficacy i.e. transformation of information security, policy and e-Governance on the Digital India programme. Findings: On developing the SAP-LAP framework, it was found that actors like the Ministry of Electronics and Information Technology of the Govt. of India secures a higher rank in implementing various initiatives and central sector schemes to accelerate the agenda of e-Governance. Actions of other preferred actors include more investments in IT infrastructure, policy development and a mechanism to address cyber security threats for effective implementation of e-Governance. It was found that actors should be pro-active on enhancing technical skills, capacity building and imparting education related to ICT applications and e-Governance. Decision making should be based on the sustainable management practices of e-Governance projects implementation to manage change, policy making and the governmental process of the Indian administration and also to achieve Sustainable Development Goals by the Indian economy. Research limitations/implications: The SAP-LAP synthesis is used to develop the case study. However, few other qualitative and quantitative multi criteria decision making approaches could also be explored for the development of IT security based e-Governance framework in the Indian context. Practical implications: The synthesis of SAP leads to LAP components which can bridge the gaps between information security, IT policy governance and e-Governance process. Based on the learning from the Situation, it is said that the case study can provide decision making support and has impact on the e-Governance process i.e. may enhance awareness about e-services available to the general public. Such work is required to assess the transparency and accountability on the Government. Social implications: Learning based on the SAP-LAP framework could provide decision making support to the administrators, policy makers and IT sector stakeholders. Thus, the case study would further help in addressing the research gaps, accelerating e-Governance initiatives and in capturing cyber threats. Originality/value: The SAP-LAP model is found as an intuitive approach to analyze the present status of information security governance, IT policy and e-Governance in India in a single unitary model.